(untitled) (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract The research aims to know and analyze the performance of honorary employees in the Academic Division of Sam Ratulangi University Manado University. The study was conducted qualitatively. The sampling technique used by the researcher is purposive sampling. Informants in this study set eight people. As informants are sub-divisions of two persons, head of one person, and five students. The focus of the study is the performance indicators, namely: Quality of Work (Quality of Work), Promptness, Initiative (Initiative), Capability (Capability), and Communication (Communication). Based on the results of the research, that the quality of work, accuracy, initiative, ability, and communication of honorary employees in the academic section of Sam Ratulangi University Manado in performing the task quite well. In general, honorary workers are educated graduates and understand how to use the computer. Although still found the results of work, is still not good, this is due to the many jobs faced. Keywords: Employee honorary, performance, quality of work (quality of work), promptness, initiative, capability, and communication.